2018
DOI: 10.12688/gatesopenres.12898.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting age-appropriate timeliness of vaccination coverage among children in Lebanon

Abstract: Background: The effect of immunization does not only depend on its completeness, but also on its timely administration. Routine childhood vaccinations schedules recommend that children receive the vaccine doses at specific ages. This article attempts to assess timeliness of routine vaccination coverage among a sub-sample of children from a survey conducted in 2016. Methods: This analysis was based on data from a cross-sectional multistage cluster survey conducted between December 2015 and June 2016 among careg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
3
9
0
Order By: Relevance
“…In terms of timeliness, we found that that almost twothird of the children were not vaccinated on-time either being early or late from the recommended time schedules. These findings corroborate the findings of other studies most of which reported higher proportion of delays in child vaccinations [10,13,27,33,49,[60][61][62][63][64] This study also pointed out that only half of fully vaccinated children were timely for all the vaccine doses. This indicates that merely relying on vaccination coverage overestimates population immunity, as it does not account for delays in protection and extended susceptibility to preventable diseases.…”
Section: Discussionsupporting
confidence: 91%
“…In terms of timeliness, we found that that almost twothird of the children were not vaccinated on-time either being early or late from the recommended time schedules. These findings corroborate the findings of other studies most of which reported higher proportion of delays in child vaccinations [10,13,27,33,49,[60][61][62][63][64] This study also pointed out that only half of fully vaccinated children were timely for all the vaccine doses. This indicates that merely relying on vaccination coverage overestimates population immunity, as it does not account for delays in protection and extended susceptibility to preventable diseases.…”
Section: Discussionsupporting
confidence: 91%
“…In terms of timeliness, we found that that almost two-third of the children were not vaccinated ontime either being early or late from the recommended time schedules. These findings corroborate the findings of other studies most of which reported higher proportion of delays in child vaccinations (10,13,27,33,49,(60)(61)(62)(63)(64) This study also pointed out that only half of fully vaccinated children were timely for all the vaccine doses. This indicates that merely relying on vaccination coverage overestimates population immunity, as it does not account for delays in protection and extended susceptibility to preventable diseases.…”
Section: Discussionsupporting
confidence: 91%
“…4, 52.26% of people who contracted measles were unvaccinated. A recent study by Mansour et al, found several factors that hinder vaccination, and these include socio-demographics, as well as knowledge, beliefs and practices associated with age-appropriate vaccination [36]. Mothers may perceive that the vulnerability to disease lessens with older age considering the first dose as the main source of protection whereas boosters are regarded as add-ons.…”
Section: Measles Cases Distribution According To Vaccination Statusmentioning
confidence: 99%